EVALUATION OF THE EFFECTIVENESS OF GROUP COOPERATION IN THE CONTEXT OF PROBLEM BASE LEARNING (PBL): A MIXED METHOD APPROACH - Subasman, Iman (LP2M IAI Al-Khairat Pamekasan, 2024)
This study uses a mixed-methods approach to evaluate the effectiveness of group collaboration in a Problem-Based Learning (PBL) context. The study integrates qualitative and quantitative analyses to understand the dynamics of group collaboration and its impact on learning outcomes. The sample consisted of 98 students involved in a semester-long PBL course. The researcher collected Quantitative data through self-assessment and peer assessment scales, while qualitative data came from in-depth interviews and analysis of group reflections. The results showed a significant correlation between group cooperation effectiveness and learning outcome achievement, with positive interaction and effective conflict management as critical factors in improving group performance. Qualitative analysis revealed that effective communication, shared leadership, and equitable task distribution enhanced group synergy. The findings provide new insights into the importance of developing collaborative skills in PBL and suggest the need for educational interventions designed to enhance group cooperation abilities. This study contributes to the PBL literature by providing empirical evidence on the effectiveness of group cooperation and its implications for teaching and learning.